100 m Long Thermally Drawn Supercapacitor Fibers with Applications to 3D Printing and Textiles. Issue 49 (4th November 2020) - Khudiyev, Tural; Lee, Jung Tae; Cox, Jason R.; Argentieri, Eric; Loke, Gabriel; Yuan, Rodger; Noel, Grace H.; Tatara, Ryoichi; Yu, Yang; Logan, Frannie; Joannopoulos, John; Shao‐Horn, Yang; et al.
Abstract: Supercapacitor fibers, with short charging times, long cycle lifespans, and high power densities, hold promise for powering flexible fabric‐based electronics. To date, however, only short lengths of functioning fiber supercapacitors have been produced. The primary goal of this study is to introduce a supercapacitor fiber that addresses the remaining challenges of scalability, flexibility, cladding impermeability, and performance at length. This is achieved through a top‐down fabrication method in which a macroscale preform is thermally drawn into a fully functional energy‐storage fiber. The preform consists of five components: thermally reversible porous electrode and electrolyte gels; conductive polymer and copper microwire current collectors; and an encapsulating hermetic cladding. This process produces 100 m of continuous functional supercapacitor fiber, orders of magnitude longer than any previously reported. In addition to flexibility (5 mm radius of curvature), moisture resistance (100 washing cycles), and strength (68 MPa), these fibers have an energy density of 306 μWh cm −2 at 3.0 V and ≈100% capacitance retention over 13 000 cycles at 1.6 V. To demonstrate the utility of this fiber, it is machine‐woven and used as filament for 3D printing. Abstract : A flow‐based preform‐to‐fiber (top‐down) thermal drawing process is used in which a preform of macroscale dimensions, assembled with all the five component materials, is thermally drawn into 100 m lengths of fully functional supercapacitor fiber. The cell architecture is designed to address the mechanical, environmental, electrical, and storage requirements of a textile and 3D printed energy‐storage device.